PEMBELAJARAN MULTIKULTURAL PADA TINGKAT SEKOLAH DASAR - Toifur Toifur (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2012)
Abstract : Indonesia is a nation of multicultural nations; diverse in the religious (Islam, Christianity, Confucianism, Protestantism, Hinduism, and other faith schools), as well as in aspects of language, ethnicity, race, and other cultures. The important of Multiculturalism to invest in education, so that learners have the knowledge, understanding, and appreciation of the diversity of people. Without the cultivation of multiculturalism, the learners will be isolated from the outside of her culture. Transformation of multicultural school level can be done through: (1) content integration), (2) knowledge construction process, (3) equity pedagogue, and, (4) empowering school structure and social structure. Key Words: Learning, Multicultural, Students.